Design and Application in Delivery System of Intranasal Antidepressants - Xu, Jingying; Tao, Jiangang; Wang, Jidong (Frontiers in Bioengineering and Biotechnology, 2020)
One of the major reasons for depressed patients that failed in treatment results from the existence of the blood-brain barrier (BBB), which prevented drug from delivering to central nervous system (CNS). In recent years, nasal drug delivery, have achieved better systemic bioavailability and activity in low doses in antidepressant treatment. In this review, we focused on the latest strategies of delivery carrier (or formation) of intranasal antidepressants. We began this review with an overview of the nasal drug delivery systems, including nasal drug delivery route, absorption mechanism, advantages and limitations in nasal drug delivery route. Next, we introduced the development of nasal drug delivery devices, such as powder devices, liquid based devices and so on. Finally, intranasal delivery carriers of antidepressants including nanogels, nanostructured lipid, liposomes nanoparticles, nanoemulsions /microemulsion in clinical studies were summarized. Moreover, challenges and future perspectives in recent progresses of intranasal delivery carriers in antidepressant treatment were discussed.